2017
DOI: 10.1016/j.jid.2017.07.699
|View full text |Cite
|
Sign up to set email alerts
|

503 Effects of blue light on inflammation and skin barrier recovery following acute perturbation

Abstract: Topically applied Imiquimod has been shown to induce psoriasis-like skin inflammation in mice. The use of larger animals such as rats would enable the use of clinical research techniques. We therefore characterized the psoriasis-like inflammation in the Imiquimod rat model using the technique of dermal Open Flow Microperfusion (dOFM) for sampling of biomarkers in inflamed and healthy skin. Psoriasis-like skin inflammation was induced on a skin test site of Sprague-Dawley rats by applying a daily dose of topica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…In another reconstructed model with Chinese-origin cells, IL-6 and IL-8 were released after UVA exposure (26), and it has also been shown that IL-8 increases in human skin after UV radiation exposure (28). Regarding blue light, contrarily to our results, one study determined that exposure to blue light did not increase IL-1α levels in the forearms of healthy volunteers, however the doses used were much lower than the doses in our study (29). Also, it is proven that blue light induces IL-1α, IL-6, and IL-8 in NHEK keratinocytes (4).…”
Section: Discussionsupporting
confidence: 50%
“…In another reconstructed model with Chinese-origin cells, IL-6 and IL-8 were released after UVA exposure (26), and it has also been shown that IL-8 increases in human skin after UV radiation exposure (28). Regarding blue light, contrarily to our results, one study determined that exposure to blue light did not increase IL-1α levels in the forearms of healthy volunteers, however the doses used were much lower than the doses in our study (29). Also, it is proven that blue light induces IL-1α, IL-6, and IL-8 in NHEK keratinocytes (4).…”
Section: Discussionsupporting
confidence: 50%